Video Self-Modeling Is an Effective Intervention for an Adult with Autism. (3rd September 2014) - Tsui, Genevieve Hin Ha; Rutherford, M. D.
Abstract : With the increases in size and strength that come with adulthood, challenging behaviours among those with autism spectrum disorders (ASD) can become critical. Few studies have explored behavioural interventions in adults with ASD, though recent studies have shown video self-modeling (VSM) to be effective in children with ASD. VSM involves an individual watching videos of himself demonstrating prosocial behaviours, while those behaviours are pointed out and encouraged. In the current study, VSM was used to encourage prosocial behaviours and to reduce problematic behaviour displayed by an adult with ASD. Results reveal a decrease in the tendency to invade others' personal space and make inappropriate loud noises. VSM may be an effective intervention and improve the lives of adults with ASD.